Dividend policy and stock price volatility of listed firms in Sri Lanka - Tharsika, K. (Rajarata University of Sri Lanka, 2023)
Maximizing the wealth of the company's shareholders' wealth is any business's primary objective (Purwanti, 2020). The shareholders' wealth is directly related to the company's market value as determined by the share price (Lingesiya & Jeyan Suganya, 2021). The movement of share prices can be either bullish (up) or bearish (down), known as Stock Price Volatility (SPV) (Mohanavel et al., 2022). The determination of share price depends upon various elements, with the primary determinant being the interplay between the demand and supply of a particular share within the market. It mainly depends on the proportion of dividends paid out by a particular company because investors buy company shares to receive a more significant return on their investment (Masum, 2014). Dividend policy plays a crucial role in determining a firm's financial health and value. Management must make an essential decision to balance the interests of shareholders and the company's growth prospects. The impact of dividend policy on stock price volatility has been extensively studied in various countries, but limited research has been conducted in the context of Sri Lanka (Lingesiya & Jeyan Suganya, 2021). Therefore, this study aims to fill this gap and shed light on the relationship between dividend policy and stock price volatility in Sri Lankan listed companies. According to Hussainey et al. (2011), there was a significant negative relationship between the dividend policy of a firm and the volatility of its stock price and a weak positive relationship between dividend yield and stock price volatility. However, Gunaratne et al. (2015) revealed that dividend yield negatively impacts stock price volatility, and the dividend payout ratio indicates a positive insignificant relationship with share price volatility. Hence, the unavailability of consensus between the previous researchers is essential to the subject of extensive research in the field of finance. This study aims to investigate the impact of dividend policy variables (such as dividend yield, dividend payout ratio, and dividend per share) on stock price volatility and provide insights and recommendations for companies and investors regarding the optimal dividend policy to minimize stock price volatility.